Using Facebook Metrics to Measure Student Engagement in Moodle - Magno, Leonardo (International Journal on Open and Distance e-Learning, 2016)
Facebook uses engagement rates as a metric for social media managers and marketers to measure how effectively a page, a post, a comment, a brand, or a topic is able to engage the target audience. Studies have proposed the use of these metrics for other types of online measurements in applications and industries other than social media. This concept paper proposes the use of a modified Facebook engagement rate formula to (i) measure students’ engagement with forum posts using virtual learning environments such as Moodle and (ii) get data from students regarding which topics or posts engage them more in the learning process. While virtual learning environments have their own logs and learning analytics software, and studies have explored the use of Facebook as a discrete and supplementary platform to traditional learning management systems, this paper fills the research gap by applying Facebook’s engagement rate formula to Moodle itself. Applying an existing social media audience engagement formula to an online course may provide instructors and educational institutions valuable feedback on what types of posts, comments, or topics make students interact and engage more in online learning sessions. Such an exercise may lead to new metrics which distance learning institutions could use to calibrate their content with the objective of improving students’ interaction and engagement with instructors, fellow students, and the online course in general.